Pengaruh Model Problem Based Learning Terhadap Hasil Pembelajaran Menulis Teks Eksposisi SMA Negeri 8 Makassar - Ikha Indawati; Hajrah; Evi Susianti (INDONESIAN LANGUAGE TEACHING & LITERATURE JOURNAL, 2026)
The Influence of Problem Based Learning Model on Writing Skills of Exposition Texts of Class XII SMA Negeri 8 Makassar aims to: (1) describe the writing skills of exposition texts of Class XII students of SMA Negeri 8 Makassar before using the problem based learning model; (2) describe the writing skills of exposition texts of Class XII students of SMA Negeri 8 Makassar after using the problem based learning model; and (3) test the influence of using the problem based learning model on the learning outcomes of writing exposition texts of Class XII students of SMA Negeri 8 Makassar. This research is a type of quantitative research. The research design used is the One Group Pretest-Posttest Design. The results of data analysis show that: (1) the learning outcomes of learning to write exposition texts of Class XII students of SMA Negeri 8 Makassar before using the problem based learning model are categorized as less skilled with an average value of 63.75; (2) the learning outcomes of learning to write exposition texts of Class XII students of SMA Negeri 8 Makassar after using the problem based learning model are categorized as quite skilled with an average value of 84.35; (3) the results of the hypothesis test show that the sig. (2-tailed) value is 0.000 < 0.05, so the alternative hypothesis (Ha) is accepted, namely that there is an influence of the use of problem-based learning on the learning outcomes of writing expository texts for Class XII students of SMA Negeri 8 Makassar. problem-based learning model, writing skills, expository text